Hydrothermal synthesis of highly fluorescent and non-toxic carbon dots using Stevia rebaudiana Bertoni - Ansari, Fatemeh; Kahrizi, Danial (Cellular and Molecular Biology, 2018)
Herein, green, environmental-friendly and economical synthesize of luminescent carbon dots (CDs) was reported using the plant-based material, Stevia rebaudiana Bertoni, as a herbal bio-sweetener. In this regard, hydrothermal carbonization of Stevia was performed under mild conditions and without any chemical oxidizing agents. Exploring the morphological aspect, surface groups, chemical composition and structure of Stevia-based CDs have been carried out systematically using SEM-EDS, TEM, fluorescence, FT-IR, UV-Vis, and XRD techniques. UV–Vis spectra displayed signature absorption of CDs at 240 nm related to the Ï€âˆ’Ï€* transitions of C=C. Fluorescence spectra showed characteristic emission at the peak wavelength of 431 nm with a quantum yield of approximately 17.5%. Moreover, there was no living cell cytotoxicity for the as-prepared CDs confirmed by confocal microscopy. These results indicated that these plant-based CDs are ideal non-toxic promising markers for cellular bio-imaging.